2003
DOI: 10.3759/tropics.12.147
|View full text |Cite
|
Sign up to set email alerts
|

Site-independent allometric relationships for estimating above-ground weights of mangroves

Abstract: Site-independent allometric relationships for above-ground weight were studied for three groups of mangroves: Rhizophora, Bruguiera, and other species. A hundred and one tree samples were collected from five forest sites where a major difference is geographical locality. For stem weight, a site-independent allometric relationship using the variable DBH'H or DROiH (D"", = stem diameter at 30 cm above the highest prop root) was attained for each group, because the specific gravity of wood and overall stem shape … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…In most studies, D/G (diameter/girth at breast height, 1.3 m from ground) was taken as the only independent variable in the allometric equation [12,13]. However, incorporation of the variable H (tree height i.e., the use of D 2 H/G 2 H) ensures higher accuracy of allometric estimation in some tree species [14,15]. Moreover, the use of the new variable D 2 0.1…”
Section: Introductionmentioning
confidence: 99%
“…In most studies, D/G (diameter/girth at breast height, 1.3 m from ground) was taken as the only independent variable in the allometric equation [12,13]. However, incorporation of the variable H (tree height i.e., the use of D 2 H/G 2 H) ensures higher accuracy of allometric estimation in some tree species [14,15]. Moreover, the use of the new variable D 2 0.1…”
Section: Introductionmentioning
confidence: 99%
“…In most studies, D (DBH) was taken as the only independent variable in the allometric equation (e.g., Nakasuga 1979;Putz and Chan 1986;Day et al 1987;Clough and Scott 1989;Amarasinghe and Balasubrananiam 1992;Mackey 1993;Clough et al 1997;Ong et al 2004). However, incorporation of the variable H (tree height) (i.e., the use of D 2 H) may ensure higher accuracy of biomass estimation (Suzuki and Tagawa 1983;Tamai et al 1986;Kusmana et al 1992;Komiyama et al 2000;Poungparn et al 2002).…”
mentioning
confidence: 98%
“…Similarly, the use of D B (stem diameter at a height of clear bole length) provides better results in estimating the weight of branch and leaf, and leaf area per tree, as described by the pipe model theory of Shinozaki et al (1964). Poungparn et al (2002) considered D B for estimating branch and leaf weight in several mangroves. However, no studies to date have considered D 0.1 2 H as an independent variable for estimating the biomass of mangroves.…”
mentioning
confidence: 99%
“…However, for the D. sissoo plantations studied the stem dbh alone showed a very strong accuracy of estimation (R 2 = 0.983 to 0.997) especially when used as D 2 . Thus, it is concluded that the use of tree height in the allometric equation (Suzuki & Tagawa 1983, Kusmana et al 1992, Poungparn et al 2002, Khan et al 2005 can be neglected for D. sissoo, as far as the present study area is con cerned. Therefore, for estimating the stem volume of sissoo, the use of D 2 as an inde pendent variable in the allometric equation with a linear or quadratic equation is recom mended.…”
Section: Discussionmentioning
confidence: 70%
“…In most studies, D (dbh, stem diameter at 1.3 m height above the ground) was taken as the only independent variable in the allo metric equation (e.g., Nakasuga 1979, Putz & Chan 1986, Clough & Scott 1989, Am arasinghe & Balasubrananiam 1992, Clough et al 1997, Ong et al 2004). However, in corporation of the variable H (tree heighti.e., the use of D 2 H) ensures higher accuracy of allometric estimation in some tree species (Suzuki & Tagawa 1983, Tamai et al 1986, Kusmana et al 1992, Poungparn et al 2002. Moreover, the use of the new variable D0.1 2 H (D0.1, diameter at one-tenth of H) instead of D 2 H has been suggested to improve the ac curacy of estimation (Ogawa & Kira 1977, Hagihara et al 1993, Khan et al 2005).…”
mentioning
confidence: 99%